INDONESIA’S FUEL SUBSIDY A SAD HISTORY OF MASSIVE POLICY FAILURE - Dick, Howard (Masyarakat Indonesia, 2013)
In her path-breaking economic history of Indonesia, ‘A History of Missed Opportunities’, Anne Booth aptly summarizes the sad history of fuel policy in Indonesia since 1980. The escalation of fuel subsidies whenever there is an upward trend in international prices and the failure to terminate them when prices fall should alert economists to some very discomforting messages. First, governments are not receptive to policy measures that involve short-term political pain and have very little awareness or interest in opportunity cost. Second, while governments pay lip service to the environment and express concern about global warming, they are not yet willing to make it a policy priority. Third, populism is the very essence of politics and has become more so in the democratic era. The lesson of history is that governments cannot be trusted to set energy prices. Nor is there any good reason to do so. What governments should do is to monitor the prices being set by Pertamina as a stateowned monopoly and provide temporary welfare support if and when it can be justified by any sudden escalation in domestic prices.